ChemInform Abstract: Enantioselective Addition of Diethylzinc to Aldehydes Catalyzed by Aziridine Carbinols. Issue 49 (December 2015) - Wang, Xiaojuan; Zhao, Wenxian; Li, Gaowei; Liu, Guanjun; Wang, Jin; Wang, Mincan; Liu, Lantao
Abstract: The enantiopure aziridine carbinol ligands are easily prepared in five steps from commercially available starting materials and successfully used as catalyst in the synthesis of chiral secondary alcohols.